We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
70
1
avatar

If f(x) = x^2-2x+1 and g(x) = sqrt{2x+1} what is the value of f(g(4)) - g(f(3))?

 May 21, 2019
 #1
avatar+102417 
+3

f(x)  = x^2 - 2x + 1

g(x)  = sqrt (2x + 1)

g(4)  = sqrt(2 * 4 + 1)  =  sqrt (9)  = 3

f(3) = (3)^2 - 2(3) + 1  =  4

 

So

 

f(g(4) ) - g(f(3)  =

 

f(3) - g(4)  =

 

4 -  3  =

 

1

 

 

cool cool cool

 May 22, 2019

6 Online Users